Acrocordiella yunnanensis sp. nov. (Requienellaceae, Xylariales) from Yunnan, China - Dissanayake, Lakmali S.; Maharachchikumbura, Sajeewa S.n.; Mortimer, Peter E.; Hyde, Kevin D.; Kang, Ji-Chuan (Phytotaxa, 2021)
Acrocordiella yunnanensis sp. nov. is introduced here from dead twigs of an unidentified dicotyledonous host from Xishuangbanna Prefecture, Yunnan Province, China. Phylogenetic analyses based on LSU and ITS sequence data revealed that this new species with a distinct sexual morph belongs to Requienellaceae (Sordariomycetes, Ascomycota). Acrocordiella yunnanensis is closely related to Acrocordiella omanensis in Requienellaceae. This novel taxon is illustrated, described, and a morphology-based key is provided to facilitate the identification of species in Acrocordiella.